Transcriptional and Post-transcriptional Regulation of Lignin Biosynthesis Pathway Genes in Populus - Zhang, Jin; Tuskan, Gerald A.; Tschaplinski, Timothy J.; Muchero, Wellington; Chen, Jin-Gui (Frontiers in Plant Science, 2020)
Lignin is a heterogeneous polymer of aromatic subunits derived from phenylalanine. It is polymerized in intimate proximity to the polysaccharide components in plant cell walls and provides additional rigidity and compressive strength for plants. Understanding the regulatory mechanisms of lignin biosynthesis is important for genetic modification of plant cell wall for agriculture and industry. Over the past 10 years the transcriptional regulatory model of lignin biosynthesis has been established in plants. However, the role of post-transcriptional regulation is still largely unknown. Increasing evidence suggests that lignin biosynthesis pathway genes are also regulated by alternative splicing, microRNA, and long non-coding RNA. In this review, we briefly summarize recent progress on the transcriptional regulation, then we focus on reviewing progress on the post-transcriptional regulation of lignin biosynthesis pathway genes in woody model plant Populus.